Threshold Values of Sleep Spindles Features in Healthy Adults Using Scalp‐EEG and Associations With Sleep Parameters - Julien Coelho; Heloïse Degros; Jean‐Arthur Micoulaud‐Franchi; Patricia Sagaspe; Emmanuel d'Incau; Paul Galvez; Christian Berthomier; Pierre Philip; Jacques Taillard (Annals of Clinical and Translational Neurology)
ABSTRACT Objective Sleep spindles are an electrophysiological fingerprint of the sleeping human brain. They can be described in terms of duration, frequency, amplitude, and density, and vary widely according to age and sex. Spindles play a role in sleep and wake functions and are altered in several neurological and psychiatric disorders. This study established the first threshold values for sleep spindles in healthy adults using scalp‐EEG and explored their associations with other sleep parameters. Methods This observational prospective study was conducted with 80 healthy participants stratified by age and sex (40.9 years, range 19–74, 50% females). All participants underwent in‐laboratory polysomnography. Sleep spindles during N2 were analyzed using an automated procedure and categorized as fast (> 13 Hz) or slow (≤ 13 Hz). Results For fast spindles, the threshold values were duration (0.80–1.11 s), frequency (13.4–14.3 Hz), amplitude (5.2–15.2 μV), and density (1.0–5.8 spindles/min). For slow spindles, the values were duration (0.79–1.17 s), frequency (12.3–12.9 Hz), amplitude (4.1–13.2 μV), and density (0.03–3.15 spindles/min). From age 40 onwards, the density, amplitude, and duration of both types of spindles decreased; the amplitudes of both types of spindles were higher in females. Higher amplitude in fast spindles was associated with increased excessive daytime sleepiness and an increased proportion of slow‐wave sleep. Interpretation This study provides the first threshold values for sleep spindle characteristics in healthy adults. The findings emphasize the importance of investigating spindles to develop innovative biomarkers for neurological and psychiatric disorders and to gain deeper insights into the functioning of the sleeping brain.